Active users’ knowledge-sharing continuance on social Q&A sites: motivators and hygiene factors - Kang, Minhyung (Aslib Journal of Information Management, 2018)
Purpose: The purpose of this paper is to focus on active users who are key contributors to online social question-and-answer (Q&A) sites, and examine antecedents of their knowledge-sharing continuance intention, based on expectation-confirmation theory and organizational justice theory. Design/methodology/approach: Sample data were gathered via an online survey from active users of Naver Knowledge-iN, a popular online social Q&A site in South Korea. Partial least squares structural equation modeling was adopted for data analysis. Moreover, a multi-group analysis was conducted to identify the motivators and hygiene factors of the responders’ knowledge-sharing continuance. Findings: Except for perceived self-worth, all the antecedents – perceived playfulness, confirmation, perceived justice with sites, and perceived justice with askers – seemed to have a considerable influence on active users’ satisfaction, and therefore their continuance intention. Among them, perceived playfulness was proven to be a motivator, and perceived justice with sites a hygiene factor. Research limitations/implications: Despite the limitations of a cross-sectional study, this research successfully illustrated that active users’ continuance intention is influenced by perceived playfulness, and not by perceived self-worth. In addition, perceived justice with social Q&A sites was proven to decrease dissatisfaction (i.e. hygiene factor), while perceived playfulness was proven to increase satisfaction (i.e. motivator). Originality/value: This study differentiates itself from prior research by focusing specifically on active users of social Q&A sites, since their motivating mechanisms are different from normal users. Additionally, the antecedents of knowledge-sharing continuance were categorized into motivators and hygiene factors. This approach affords detailed guidelines to facilitate active users’ knowledge-sharing continuance and to prevent their defection.
Keywords: Continuance intentions; Expectation Confirmation Theory; Knowledge-sharing; Organizational justice theory; Social question-and-answer sites; Two-factor theories; Continuance intention; Expectation-confirmation theory; Knowledge sharing; Organizational justice theory; Social question-and-answer sites; Two-factor theory